Kajian Naratologi Genette Dalam Tiga Cerita Pendek Pilihan Kompas Tahun 2000an - Sufi Ikrima Sa'adah (Jurusan Sastra Indonesia, 2018)
This research studies the narrative aspect in three selected Indonesian short stories based on Kompas in year 2000s. The theoretical framework applied is Genette’s narratology focusing on duration, focalization, and person. This study is library research using descriptive analytical method by conducting close reading. The result says that the narrative aspect in each story implies the society’s attitude towards specific problem portrayed in the stories.